Triterpenoids From Alisma Species: Phytochemistry, Structure Modification, and Bioactivities - Wang, Pengli; Song, Tongxin; Shi, Rui; He, Mingshuai; Wang, Rongrong; Lv, Jialin; Jiang, Miaomiao (Frontiers in Chemistry, 2020)
Plants from Alisma species belong to the genus of Alisma Linn. in Alismataceae family. The tubers of A. orientale (Sam.) Juzep, also known as Ze Xie in Chinese and Takusha in Japanese, have been used in traditional medicine for a long history. Triterpenoids are the main secondary metabolites isolated from Alisma species, and reported with various bioactive properties, including anticancer, lipid-regulating, anti-inflammatory, antibacterial, antiviral and diuretic activities. In this brief review, we aimed to summarize the phytochemical and pharmacological characteristics of triterpenoids found in Alisma, and discuss their structure modification to enhance cytotoxicity as well.